Pelatihan dan Pendampingan Pemanfaatan Sistem Informasi Akademik bagi Civitas Akademik SMP Negeri 4 Kecamatan Rambutan - Novri Hadinata; Eka Puji Agustini; Kurniawan Kurniawan; Nyimas Sopiah; Bella Rosalia (Jurnal Nasional Pengabdian Masyarakat, 2021)
SMPN 4 Rambutan District, Banyuasin Regency is one of the junior high schools that was only established in 2019. Currently, most academic administrative activities are still carried out manually such as student data, teacher data, grades data, and attendance data are still in the form of archives, making it difficult to search for data. Based on this, it can be concluded that SMP Negeri 4 Rambutan requires a website-based academic sistem that can solve the problem, besides that training and assistance to the academic community is also needed. This activity is carried out in 3 stages, namely the delivery of materials, training and mentoring. The purpose of this activity is to make it easier for all academics in carrying out the teaching and learning process every day